2013
DOI: 10.7554/elife.01340
|View full text |Cite
|
Sign up to set email alerts
|

Structure and function of the Smoothened extracellular domain in vertebrate Hedgehog signaling

Abstract: The Hedgehog (Hh) signal is transduced across the membrane by the heptahelical protein Smoothened (Smo), a developmental regulator, oncoprotein and drug target in oncology. We present the 2.3 Å crystal structure of the extracellular cysteine rich domain (CRD) of vertebrate Smo and show that it binds to oxysterols, endogenous lipids that activate Hh signaling. The oxysterol-binding groove in the Smo CRD is analogous to that used by Frizzled 8 to bind to the palmitoleyl group of Wnt ligands and to similar pocket… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
225
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 145 publications
(251 citation statements)
references
References 92 publications
13
225
2
Order By: Relevance
“…In addition, the synergistic inhibition of Hh signaling by calcitriol and ITZ indicated that calcitriol and ITZ bind to different Smo sites. To validate the hypothesis that calcitriol binds to Smo outside the 7TM or CRD, we tested if calcitriol or ITZ might compete for direct Smo binding with BODIPY-labeled CP in HEK293S cells (20,24), because the binding sites of CP have been already mapped to the 7TM domains of Smo and to some extend to the CRD (18,20). Indeed, the known 7TM binders, CP (Fig.…”
Section: Calcitriol Efficiently Inhibits the Translocation Of Smo Intmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, the synergistic inhibition of Hh signaling by calcitriol and ITZ indicated that calcitriol and ITZ bind to different Smo sites. To validate the hypothesis that calcitriol binds to Smo outside the 7TM or CRD, we tested if calcitriol or ITZ might compete for direct Smo binding with BODIPY-labeled CP in HEK293S cells (20,24), because the binding sites of CP have been already mapped to the 7TM domains of Smo and to some extend to the CRD (18,20). Indeed, the known 7TM binders, CP (Fig.…”
Section: Calcitriol Efficiently Inhibits the Translocation Of Smo Intmentioning
confidence: 99%
“…Calcitriol Efficiently Inhibits CRD-deleted Smo-The CRD of Smo has been described as an exclusive binding site for oxysterols that are discussed to be physiological regulators of Hh signaling activity (18,19 (Fig. 3, a and b (Fig.…”
Section: Calcitriol Efficiently Inhibits the Translocation Of Smo Intmentioning
confidence: 99%
See 3 more Smart Citations